2020
DOI: 10.1063/5.0022788
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of capacitive radio-frequency discharges in nonlocal regimes

Abstract: Similarity transformations are essential for correlating discharges at different scales, which are mostly utilized with local field or local energy approximations. In this work, we report the fully kinetic results from particle-in-cell/Monte Carlo collision simulations that unambiguously demonstrate the similarity of radio frequency (rf) discharges in nonlocal regimes where the electron energy relaxation length is much larger than the gap dimension. It is found that at a constant rf voltage amplitude, discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 76 publications
7
16
0
Order By: Relevance
“…The sudden increase in the ratio of energetic electrons in the sustained plasma indicates that the plasma discharge mode transition occurs from the α to the γ mode. The results of Fu et al [11,24] validate the discharge mode transition in our experiment. Fu et al [11,24] reported that the similarity law was identified in similar discharge structures through driving frequency scaling.…”
Section: B Change In the Electron Temperaturesupporting
confidence: 87%
See 2 more Smart Citations
“…The sudden increase in the ratio of energetic electrons in the sustained plasma indicates that the plasma discharge mode transition occurs from the α to the γ mode. The results of Fu et al [11,24] validate the discharge mode transition in our experiment. Fu et al [11,24] reported that the similarity law was identified in similar discharge structures through driving frequency scaling.…”
Section: B Change In the Electron Temperaturesupporting
confidence: 87%
“…The results of Fu et al [11,24] validate the discharge mode transition in our experiment. Fu et al [11,24] reported that the similarity law was identified in similar discharge structures through driving frequency scaling. It was shown that the electron energy probability function (EEPF) overlapped when the driving frequency was varied in the α mode, demonstrating that in a similar discharge mode, the proportion of energetic electrons is maintained.…”
Section: B Change In the Electron Temperaturesupporting
confidence: 87%
See 1 more Smart Citation
“…Such conditions are most prominent in weakly collisional settings, e.g., at low pressures where the mean free path of the charged particles (typically of the electrons) can be comparable or even longer than the dimensions of the system. Under such conditions, the transport has a nonlocal character [2][3][4][5][6] and although continuum (fluid) approaches can capture this phenomenon to some extent, it is usually achieved by including the corresponding Energy/Velocity Distribution Function (EDF/VDF) and nonlocal closure of the equations as an input to the model [7]. Particle methods, on the other hand, do not require any assumptions of this kind and provide the EDF/VDF as a result of the calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The primary computational tool for these investigations has been the Particle-in-Cell/Monte Carlo Collisions (PIC/MCC) simulation. [55][56][57][58] This particle based approach is fully capable to capture kinetic effects, 59 therefore is well suited for the description of plasma sources operated at low pressures where non-local particle transport [60][61][62][63] appears. An analytical model 27 based on the voltage balance of the discharge has aided the understanding of the observations.…”
Section: Introductionmentioning
confidence: 99%